Srpski - Boskovic, Milica; Jankovic, Brankica (Serbian political thought, 2024)
The challenges societies and countries are facing both at the national and global level at modern times, show, more than ever, the significant impact for the implementation of the concept of human security. Poverty, unequal access to education and employment, violation of human rights and settlement among people and social groups, destabilize states, and therefore the pillars of national security. Discrimination and violence against one large group in society - women, on a global level has shown that such conditions at society and actual norms cannot lead to stability and a conflict-free future. A society that has weak response mechanisms to violence against women, their discrimination at economic terms, and at the chances to find themselves in key positions in political and security structures, basically cannot understand the concept of well-being, peace, and progress. UN Security Council Resolution 1325 and action plans for its implementation at the national and local level make a significant contribution for overcoming these entrenched stereotypes and today’s security challenges. This Article presents the results of the implementation of national action plans at our country, which resulted from Resolution 1325, better known as "Women, peace and security". Thanks to the various analyzes of governmental and non-governmental institutions, it is possible to review the successes made so far, but also provided base for recommendations for further strengthening the mechanisms for achieving gender equality and improving human security in our country. At this Article, such recommendations are provided, based on previously shown data and descriptive explanations about improvements and gaps at our country.